Incy wincy spider - Chapman, Keith; Tickle, Jack (London : Little Tiger Press, 2005)
Incy wincy Spider, playing on a farm, Spinning silver silk webs high up in a barn. From an open window a gust of wind blows Whoooo! And Incy Wincy Spider with a Whoooooosh goes too!
Keywords: Farm animals -- Fiction; Spiders -- Fiction